2019
DOI: 10.1021/acsaelm.9b00366
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of Free-Standing Bismuth Film on Graphene Embedded with Nontrivial Properties

Abstract: Topological insulators (TIs) have become one of the intensely pursed topics during the past few years due to their robust gapless edge states, among which bismuth (Bi) enjoys a good reputation because of its rich quantum states. However, bulk Bi itself is topologically trivial. While thin Bi film has long been theoretically perceived to be a two-dimensional topological insulator, it still remains a challenge to construct free-standing Bi(111) film experimentally. Herein, we investigate the epitaxial growth of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 53 publications
(90 reference statements)
0
20
0
Order By: Relevance
“…The periodicity of Bi(111) thin film is around 4.7 Å, as shown in Fig. 1c, which is larger than the lattice constant (~ 4.54 Å ) of 7-layer Bi(111) thin film grown on graphene/SiC substrate but comparable to that (~ 4.75 Å ) of monolayer Bi(111) on single-layer Bi(110) with the support of highly oriented pyrolytic graphite 25,26 .…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The periodicity of Bi(111) thin film is around 4.7 Å, as shown in Fig. 1c, which is larger than the lattice constant (~ 4.54 Å ) of 7-layer Bi(111) thin film grown on graphene/SiC substrate but comparable to that (~ 4.75 Å ) of monolayer Bi(111) on single-layer Bi(110) with the support of highly oriented pyrolytic graphite 25,26 .…”
mentioning
confidence: 88%
“…The bismuth thin film displays the thickness dependent facet on the surface of graphene at room temperature, where a crystalline transition from (110)-orientated facet with the black phosphorus-like structure to (111)-orientated facet with the buckled honeycomb structure occurs after the layer number increases up to a critical value 25 . The similar growth dynamics have also been identified in our results, as shown in Supplementary Fig.…”
mentioning
confidence: 99%
“…[ 44a ] In particular, its in‐plane anisotropic properties, which arise from the puckered structure, [ 152 ] have inspired the intensive exploration of other isoelectronic materials [ 45 ] and Group VA elemental analogs. [ 11d,153 ] In addition to phosphorous, arsenic, antimony [ 154 ] and bismuth [ 155 ] have all been established as semiconducting materials by calculations as well as experiments during the last several years. [ 18b ] We will address recent achievements in the epitaxial growth of these elemental graphene analogs on various types of substrates.…”
Section: Epitaxial Growth Of Me2dmsmentioning
confidence: 99%
“…Such layer‐dependent phase transition has also been observed during the growth of Bi on graphite and graphene surfaces. [ 155 ]…”
Section: Epitaxial Growth Of Me2dmsmentioning
confidence: 99%
“…[37][38][39]110] Figures 2c,d shows the top and side views of the αand β-bismuthene, which exhibit a puckered black-phosphorus-like structure and a buckled graphene-like structure corresponding to the Bi (110) and Bi (111) plane, respectively. Ab initio molecular dynamics simulations indicated that both geometries have good thermal stability and could keep stable up to 700 K. [111] Experimentally, Bi prefers the formation of α-bismuthene film at a small thickness when deposited on Si(111), [110a] highly oriented pyrolytic graphite (HOPG), [110b,c] 1TÀ TaS 2 [37] and graphene/SiC substrates, [36] while β-bismuthene is favored for thicker film. For example, upon reducing the thickness of Bi films from 8 layers to 2 layers on the 1TÀ TaS 2 , the 2D Bi films underwent a structural transition from buckled to puckered structure.…”
Section: Bimentioning
confidence: 99%